2022
DOI: 10.1016/j.jocn.2021.11.023
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of glioblastoma with re-purposed renin-angiotensin system modulators: Results of a phase I clinical trial

Abstract: Glioblastoma is the most common and most aggressive primary brain cancer in adults. Standard treatment of glioblastoma consisting of maximal safe resection, adjuvant radiotherapy and chemotherapy with temozolomide, results in an overall median survival of 14.6 months. The aggressive nature of glioblastoma has been attributed to the presence of glioblastoma stem cells which express components of the renin-angiotensin system (RAS). This phase I clinical trial investigated the tolerability and efficacy of a treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…Despite advancements in multimodal treatment modalities, glioblastoma remains a devastating disease with poor prognosis and rare long-term survival. , Studies have shown promising results with curcumin in treating glioblastoma. For example, in a phase I dose escalation study, after the administration of renin-angiotensin system blockers, i.e., curcumin, propranolol, aliskiren cilazapril, celecoxib, piperine, aspirin, and metformin (piperine was ingested to enhance the absorption of curcumin), an increase in median survival (not statistically significant) was observed in patients with advanced-stage relapsed glioblastoma with a Karnofsky performance score of at least 60 ( n = 10) . In another study, Esposito et al demonstrated that dietary supplementation with 1200 mg/day curcumin reduced the number and volume of cutaneous neurofibromas in patients with neurofibromatosis I, which is an autosomal dominant disorder associated with a predisposition to tumor development, including glioma ( n = 11) …”
Section: Clinical Trials Of Turmeric and Curcuminmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite advancements in multimodal treatment modalities, glioblastoma remains a devastating disease with poor prognosis and rare long-term survival. , Studies have shown promising results with curcumin in treating glioblastoma. For example, in a phase I dose escalation study, after the administration of renin-angiotensin system blockers, i.e., curcumin, propranolol, aliskiren cilazapril, celecoxib, piperine, aspirin, and metformin (piperine was ingested to enhance the absorption of curcumin), an increase in median survival (not statistically significant) was observed in patients with advanced-stage relapsed glioblastoma with a Karnofsky performance score of at least 60 ( n = 10) . In another study, Esposito et al demonstrated that dietary supplementation with 1200 mg/day curcumin reduced the number and volume of cutaneous neurofibromas in patients with neurofibromatosis I, which is an autosomal dominant disorder associated with a predisposition to tumor development, including glioma ( n = 11) …”
Section: Clinical Trials Of Turmeric and Curcuminmentioning
confidence: 99%
“…For example, in a phase I dose escalation study, after the administration of renin-angiotensin system blockers, i.e., curcumin, propranolol, aliskiren cilazapril, celecoxib, piperine, aspirin, and metformin (piperine was ingested to enhance the absorption of curcumin), an increase in median survival (not statistically significant) was observed in patients with advanced-stage relapsed glioblastoma with a Karnofsky performance score of at least 60 (n = 10). 270 In another study, Esposito et al demonstrated that dietary supplementation with 1200 mg/day curcumin reduced the number and volume of cutaneous neurofibromas in patients with neurofibromatosis I, which is an autosomal dominant disorder associated with a predisposition to tumor development, including glioma (n = 11). 271 Head and neck squamous cell carcinoma is the sixth most frequently occurring cancer and belongs to the challenge-totreat category of malignancies.…”
Section: Clinical Trials Of Turmeric and Curcuminmentioning
confidence: 99%
“…We have recently presented results of a phase I clinical trial on recurrent glioblastoma by targeting CSCs in by influencing the TME to modulate the RAS using multiple medications (propranolol, aliskiren, cilazapril, celecoxib, curcumin with piperine, aspirin, and metformin) [ 254 ]. The treatment was well tolerated with low side-effects, and the quality of life and performance status of the participants were preserved during treatment with an overall median survival 19.9 months [ 254 ]. The increased survival of 5.3 months, although not statistically significant, was encouraging, and warrants further investigation.…”
Section: Therapeutic Interventions For Cancer Metastasis and Treatmen...mentioning
confidence: 99%
“…Targeting the RAS, its bypass loops and converging signaling pathways to achieve optimal blockade of the RAS to regulate CSCs has been proposed ( 3 5 ). This “hollistic” approach of blocking the RAS at multiple points simultaneously, forms the basis of a phase I clinical trial for recurrent glioblastoma ( 187 ) resulting in a trend toward increased survival by 5.3 months. The encouraging results of this trial warrant further clinical trials on this novel, well-tolerated and cost-effective potential therapeutic option for patients with glioblastoma, and potentially other cancer types.…”
Section: Cancer Stem Cells and The Renin-angiotensin System In Cancermentioning
confidence: 99%
“…This offers an exciting opportunity in developing novel therapeutic approaches to achieve optimal modulation of the crucial and complex system by further investigations. This novel approach of blocking the RAS at multiple points simultaneously forms the basis of a phase I clinical trial for glioblastoma ( 187 ). The encouraging results of this trial warrant further clinical trials on this potential novel, well-tolerated and cost-effective therapeutic option for patients with glioblastoma, and potentially other cancer types.…”
Section: Targeting the Renin-angiotensin System In Vascular Anomalies...mentioning
confidence: 99%